(untitled) (Swiss Medical Weekly, 2024)
AIMS: Anthracycline-based chemotherapy has well-known cardiotoxic effects, butmay also cause skeletal muscle myopathy and negatively affect cardiorespiratory fitness and quality of life. The effectiveness of exercise training in improving cardiorespiratory fitness and quality of life during chemotherapy is highly variable. We set out to determine how the effect of exercise training on cardiorespiratory fitness (primary outcome) and quality of life (secondary outcome) in cancer patients is affected by the type of therapy they receive (cardiotoxic therapy with or without anthracyclines; non-cardiotoxic therapy) and the timing of the exercise training (during or after therapy). METHODS: Consecutive patients with cancer who participated in an exercise-based cardio-oncology rehabilitation programme at a university hospital in Switzerland between January 2014 and February 2022 were eligible. Patients were grouped based on chemotherapy (anthracycline vs non-anthracycline) and timing of exercise training (during vs after chemotherapy). Peak oxygen uptake (VO2) was assessed with cardiopulmonary exercise testing (n = 200), and quality of life with the Functional Assessment of Cancer Therapies questionnaire (n = 77). Robust linear models were performed for change in peak VO2 including type and timing of cardiotoxic therapies, age, training impulse and baseline peak VO2; change in quality of life was analysed with cumulative linked models. RESULTS: In all patients with valid VO2 (n = 164), median change in peak VO2 from before to after exercise training was 2.3 ml/kg/min (range: –10.1–15.9). The highest median change in peak VO2 was 4.1 ml/kg/min (interquartile range [IQR]: 0.7–7.7) in patients who completed exercise training during non-anthracycline cardiotoxic or non-cardiotoxic therapies, followed by 2.8 ml/kg/min (IQR: 1.2–5.3) and 2.3 ml/kg/min (IQR: 0.1–4.6) in patients who completed exercise training after anthracycline and after non-anthracycline cardiotoxic or non-cardiotoxic therapies, respectively. In patients who completed exercise training during anthracycline therapy, peak VO2 decreased by a median of –2.1 ml/kg/min (IQR: –4.7–2.0). In the robust linear model, there was a significant interaction between type and timing of cancer treatment for anthracycline therapy, with greater increases in peak VO2 when exercise training was performed after anthracycline therapy. For quality of life, higher baseline scores were negatively associated with changes in quality of life. CONCLUSION: In our cohort, the increase in cardiorespiratory fitness was diminished when exercise training was performed concurrently with anthracyclines. For patients with cardiotoxic treatments other than anthracyclines, cardiorespiratory fitness and quality of life was not associated with timing of exercise training.